Pelatihan Pembuatan Produk Ekstrak Rimpang Instan dan Mie Organik Bersama Remaja Guna Meningkatkan Perekonomian Desa Jipurapah: Pelatihan Pembuatan Produk Ekstrak Rimpang Instan dan Mie Organik Bersama Remaja Guna Meningkatkan Perekonomian Desa Jipurapah - Putri, Aprilia Asya; Hidayah, Nurul; Amirta, Adinda Zakia Putri; Damayanti, Ella; Febrianti, Reyna Tifara; Zulfa, Syahdatul Nabila Indana (J.Abdimas: Community Health, 2024)
Jipurapah Village is rich in rhizome plants such as temulawak, turmeric, and lempuyang which are underutilized. The MERETAS ASA community service activity was carried out in Jipurapah Village, Plandaan District, Jombang Regency, which aims to increase knowledge for teenagers about processing rhizome plants that grow around the village and improve the village economy to be better by utilizing plants in Jipurapah Village, this community service invites Jipurapah teenagers to make an innovative product. The method used in the MERETAS ASA activity is product manufacturing training with the community, especially teenage girls. This service is carried out as one of the village programs to provide empowerment to teenage girls and cadre mothers in Jipurapah Hamlet to utilize the results of rhizome plants (Temulawak, Lempuyang, and Turmeric) as well as cassava and spinach plants. As a result of the service, the community can process natural resources from raw into instant products ready for consumption. Products that have been processed can be sold to improve the community's economy.